Causes of the Failed of the Military Coup in Turkey in 2016 - Mhd Alfahjri Sukri (UIN Sunan Gunung Djati, 2021)
Military interference in politics in Turkey resumed with an outright military coup on July 15, 2016, but the Coup failed. The Turkish military has always successfully conducted coups, both directly and indirectly, which occurred in 1960, 1971, 1980, and 1997. From these problems, The study aims to analyze the causes of the failure of the 2016 coup and describe the causes of the Coup and compare the 2016 coup with the 1960 and 1980 direct coups. A qualitative method was used in this research by conducting literature studies and data sourced from scientific journals, news reports, articles, and other related sources. The results showed that the failure of the military Coup in 2016 was due to rejection from the community but also the failure of the coup group to arrest key government actors such as President Erdogan and Prime Minister Binali Yildirim. The failure to arrest these key actors enabled them to mobilize the masses against the coup group, as did President Erdogan, who announced his rejection of the Coup through FaceTime broadcast by CNN Turk and invited the public to reject the Coup. Binali Yildirim also rejected the same problem. This is one of the factors that led to the descent of Turks to the streets against the coup attempt. Even though seeing the previous Coup, the military always received support from the Turkish people. In addition, there is also the role of technology that connects key actors with Turkish society. This research explains the important role of key state actors in countering military coups and provides an overview of ways for civilian governments and the general public to resist military coups.